1995
DOI: 10.1557/proc-395-777
|View full text |Cite
|
Sign up to set email alerts
|

(Negative) Electron Affinity of AlN and AlGaN Alloys

Abstract: The electron affinity of a semiconductor defines the relationship of the vacuum level and the semiconductor band structure. It is dependent on the atomic orbitals of the material and the surface termination. We report experimental and theoretical results that support the presence of a negative electron affinity on AlN and the Al rich AlGaN alloys. The GaN surface is found to exhibit a (positive) electron affinity of 3.3eV. The experimental measurements employ UV-photoemission spectroscopy on in situ gas-source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Compared to single-walled carbon nanotubes and ZnO nanowires, whose work functions are about 4.9 and 5.3 eV, respectively [5,6], GaN has a lower work function of 4.1 eV, stronger thermal stability, mechanical hardness, chemical stability, and a lower electron affinity of 2.7-3.3 eV [7]. Therefore, GaN cold cathodes probably obtain high electron emission current densities and low operation voltages.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to single-walled carbon nanotubes and ZnO nanowires, whose work functions are about 4.9 and 5.3 eV, respectively [5,6], GaN has a lower work function of 4.1 eV, stronger thermal stability, mechanical hardness, chemical stability, and a lower electron affinity of 2.7-3.3 eV [7]. Therefore, GaN cold cathodes probably obtain high electron emission current densities and low operation voltages.…”
Section: Introductionmentioning
confidence: 99%
“…This results in a very low potential barrier for the electron conduction from n-Si to PEDOT for the case of the ideal interface. On the other hand, from the electron affinity of 2.7-3.3 eV reported for GaN [13,14], the potential barrier of electrons from PE-DOT to GaN can be estimated to be around 2 eV. Although it causes the increase in applied voltage depending on the carrier concentration of GaN particles, this effect was not taken into consideration in the analysis of this study, which is described in the next section.…”
Section: Invitedmentioning
confidence: 97%
“…Recently, the electron affinities of III nitrides were studied by using the ultraviolet photoemission spectroscopy ͑UPS͒. 2,13 Nemanich et al 2 showed that the surfaces of GaN and Al 0.13 Ga 0.87 N exhibit the electron affinities of 3.3 and 2.9 eV, respectively. The lower electron affinity of Al 0.1 Ga 0.9 N than that of GaN accounts for enhancement of the emission current, as observed in the present results.…”
Section: N Sawakimentioning
confidence: 99%